Review on current limits and potentialities of technologies for biomedical ceramic scaffolds production. Issue 3 (14th September 2020) - Marques, Ana; Miranda, Georgina; Silva, Filipe; Pinto, Paulo; Carvalho, Óscar
Abstract: Osseointegration is defined by a stable and functional union between bone and a surface of a material. This phenomenon is influenced by the geometric and surface characteristics of the part where the bone cells will attach. A wide variety of studies proves that ceramic materials are strong competitors against conventional metals in the scope of bone tissue engineering. Ceramic scaffolds, porous structures that allow bone ingrowth, have been studied to enhance the osseointegration phenomenon. Geometric and dimensional parameters of the scaffold have influence in its performance as mechanical and structural supporter of bone growth. However, these parameters are conditioned by the manufacturing process by which these scaffolds are obtained. Several studies focusing on the production process of ceramic scaffolds have been developed, using 3D printing, stereolithography, selective laser sintering, green machining, robocasting, and others. The main purpose of this work is to evaluate and compare the different manufacturing processes by which ceramic scaffolds can be produced. This comparison addresses scaffold parameters like pore size, pore shape, porosity percentage, roughness, and so forth. Additionally, the different materials used in different manufacturing processes are also mentioned and discussed given its influence on a successful osseointegration while simultaneously displaying adequate mechanical properties. After making a screening on the available ceramic scaffolds manufacturing processes, several examples are presented, proving the potential of each of these manufacturing process for a given scaffold geometry.